Viajes, comercio y cultura corsa en el noreste venezolano (S. XIX): aproximación histórica a los estereotipos de viaje a través del documental De navíos, ron y chocolate - Edda O. Samudio Aizpurúa; Johnny V. Barrios-Barrios (Les Cahiers ALHIM)
The present work seeks to address, study and expose in an analytical way the importance of travel and travelers during the nineteenth-century, as well as some stereotypes registered around the foreign presence in Venezuela. This exercise is based on the renowned documentary De navíos, ron y chocolate (Roncayolo, 2011), where it is possible to observe the context of this historical period and the economic and sociocultural aspects about the  Corsican presence in eastern Venezuela, which allows a historical approach to the theme of travel through documentation, oral testimonies, dramatization, imaginary perspectives and evocation of historical images, elements that bring the observer closer to narratives,  representations, socio-symbolic aspects and perceptions of Venezuelan culture. The interest in this documentary lies in the fact that it allows us to claim before the new generations how in the process of emigration much of the homeland is lost, but it is gained in the host land. Venezuela has always been a land of possibilities where the legacies that are the basis of its cultural melting pot coexist harmoniously.